Southeast Research and Extension Center Agricultural Research 2019 - L. W. Lomas (Kansas Agricultural Experiment Station Research Reports, 2019)
Report on agricultural research performed at Southeast Research and Extension Center. Full book to view.
Keywords: crops; beef cattle; soil and water management; weather data; Southeast Research and Extension Center; agricultural research